(untitled) (diségno, 2019)
During the last Congress of the Unione Italiana per il Disegno, held in Naples, the 2017 UID Gold Medal was awarded to Anna Sgrosso with the aim of rewarding the complex of scientific and cultural activities promoted at the University of Naples Federico II over a long and prestigious career. Thanks to her studies, both in architectural and mathematical fields, Anna Sgrosso has revitalized Descriptive Geometry, finding new expressive and communicative impulse in the study of its projective roots and in the links that this discipline establishes with the world of figuration and art. In particular, Anna Sgrosso’s proposal to use traditional representation systems (Monge, axonometry, perspective) in an unconventional manner led to an innovative interpretation of architecture –realized or in progress–, in which it is possible to identify structure and geometric genesis of the spaces.